Emerging CAR T cell therapies: clinical landscape and patent technological routes - Virgínia Picanco-Castro; Cristiano Gonçalves Pereira; Kamilla Swiech; Kelen Cristina Ribeiro Malmegrim; Dimas Tadeu Covas; Geciane Silveira Porto (Taylor & Francis Group, 2020)
The purpose of this study is to mine CAR-T patents and therapies under development, to design a landscape of the sector and to understand key therapy segments and their current trends. The study analyzed the entire market, consisting of 1624 patent families and 509 biologics under development, to depict an overview of the CAR-T therapies and their state of the art. Our results showed cutting-edge inventions, the major players, the dynamics of cooperation among institutions, the progress of the therapies' generation over the years and future innovation pathways. CAR-T therapies are transforming the current scenario for cancer treatment, and this study reveals the picture of what we can likely expect ahead in order to assist scientists at the academy and industry to improve their research strategies.